ANALISIS PERSEPSI DAN TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN FARMASI DI RUMAH SAKIT PATUH KARYA - Hendardi, Lalu Ofan; Sastrawan, Sastrawan; Karjono, Karjono (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the level of patient perception and level of patient satisfaction as well as the relationship between these two variables on the quality of pharmaceutical services at the Patuh Karya Regional General Hospital. The method used in this study is the design in this study is observational descriptive using quantitative data based on a cross sectional approach using the ServQual model with 5 (five) dimensions of service quality, namely: Tangible, Reliability, Responsiveness (Responsivness), Assurance (Assurance) and Empathy (Emphaty). The number of samples in this study were 56 people using the sampling technique, namely accidental sampling and the samples were selected according to the inclusion criteria. The instrument used in this study was a questionnaire that was compiled based on pharmaceutical service criteria. The data analysis used in this study was a univariate test and a bivariate test with the help of SPSS. The results showed that the patient's perception of the quality of pharmaceutical services obtained results that were sufficient with a level of satisfaction (30.4%) and good (69.6%). For patient satisfaction with the quality of pharmaceutical services, the results were quite satisfied (66.1%) and satisfied (33.9%). Based on the results of statistical tests with Bivariate analysis or chi square test where this is done to see the relationship or correlation between variables, the independent variable is the patient's perception of the quality of pharmaceutical services and the dependent variable is patient satisfaction with the quality of pharmaceutical services, where the research subjects are patients outpatient care due to the Asymptotic Significance (2-sided) or p-value of 0.00 which is less than the 0.05 significance level (0.01 ≤ 0.05) so that there is a significant relationship between patient perception and satisfaction with the quality of pharmaceutical services at the Regional General Hospital Patuh Karya.